Synthesis of guanidinium–sulfonimide ion pairs: towards novel ionic liquid crystals - Butschies, Martin; Neidhardt, Manuel M.; Mansueto, Markus; Laschat, Sabine; Tussetschläger, Stefan (Beilstein Journal of Organic Chemistry, 2013)
The recently introduced concept of ionic liquid crystals (ILCs) with complementary ion pairs, consisting of both, mesogenic cation and anion, was extended from guanidinium sulfonates to guanidinium sulfonimides. In this preliminary study, the synthesis and mesomorphic properties of selected derivatives were described, which provide the first example of an ILC with the sulfonimide anion directly attached to the mesogenic unit.
Keywords: anion exchange; ionic liquid crystals; ion pairs; mesophases; sulfonimides